Normosmic idiopathic hypogonadotropic hypogonadism due to a novel GNRH1 variant in two siblings. (5th March 2020) - Sagi, Satyanarayana V; Joshi, Hareesh; Whiles, Emily; Hikmat, Mondy; Puthi, Vijith R; MacDougall, Jane; Spiden, Sarah L; Fuller, Gavin; Park, Soo-Mi; Oyibo, Samson O
Abstract : Summary: Hypogonadotropic hypogonadism is characterised by insufficient secretion of pituitary gonadotropins resulting in delayed puberty, anovulation and azoospermia. When hypogonadotropic hypogonadism occurs in the absence of structural or functional lesions of the hypothalamic or pituitary gland, the hypogonadism is defined as idiopathic hypogonadotropic hypogonadism (IHH). This is a rare genetic disorder caused by a defect in the secretion of gonadotropin releasing hormone (GNRH) by the hypothalamus or a defect in the action of GNRH on the pituitary gland. Up to 50% of IHH cases have identifiable pathogenic variants in the currently known genes. Pathogenic variants in the GNRHR gene encoding the GNRH receptor are a relatively common cause of normosmic IHH, but reports of pathogenic variants in GNRH1 encoding GNRH are exceedingly rare. We present a case of two siblings born to consanguineous parents who were found to have normosmic idiopathic hypogonadotropic hypogonadism due to homozygosity of a novel loss-of function variant in GNRH1 . Case 1 is a male who presented at the age of 17 years with delayed puberty and under-virilised genitalia. Case 2 is a female who presented at the age of 16 years with delayed puberty and primary amenorrhea. Learning points: IHH is a genetically heterogeneous disorder which can be caused by pathogenic variants affecting proteins involved in the pulsatile gonadotropin-releasing hormone release, action, or both. Currently known genetic defects account for up to 50% of all IHH cases. GNRH1 pathogenic variants are a rare cause of normosmic IHH. IHH is associated with a wide spectrum of clinical manifestations. IHH can be challenging to diagnose, particularly when attempting to differentiate it from constitutional delay of puberty. Early diagnosis and gonadotrophin therapy can prevent negative physical sequelae and mitigate psychological distress with the restoration of puberty and fertility in affected individuals.